2019
DOI: 10.1029/2019ja026723
|View full text |Cite
|
Sign up to set email alerts
|

On Deriving Gravity Wave Characteristics in the Daytime Upper Atmosphere Using Radio Technique

Abstract: The importance of neutral wave dynamics in the understanding of the upper atmospheric processes is well known. Conventionally, optical methods are used to derive information on the neutral wave dynamics by obtaining gravity wave (GW) characteristics. Optical measurement techniques use airglow emissions as tracers to obtain such information that correspond to altitudes from where the emissions emanate. However, in this paper, we describe a method using radio wave measurement technique (digisonde) to obtain info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Frequencies range are from 2 to 14 MHz with a step size of 0.05 MHz. The downward movement of the phase velocity identifies the possible presence of gravity waves in the ionosphere as was reported in many prior studies [53][54][55]. The result demonstrates that spread F and spread Es during the recovery phase of the storm might be associated with TIDs/AGWs.…”
Section: Discussionsupporting
confidence: 78%
“…Frequencies range are from 2 to 14 MHz with a step size of 0.05 MHz. The downward movement of the phase velocity identifies the possible presence of gravity waves in the ionosphere as was reported in many prior studies [53][54][55]. The result demonstrates that spread F and spread Es during the recovery phase of the storm might be associated with TIDs/AGWs.…”
Section: Discussionsupporting
confidence: 78%
“…Figure 6c shows the temporal variation of the electron density profile at Sao Luis between 12 and 24 UT on 24 October 2018. There was a clear downward phase propagation (marked with a dashed line), which identifies the possible presence of atmospheric gravity waves (AGWs) (Abdu et al, 2009;Mandal et al, 2019). Three continuous quasiperiodic (∼50 min) wave-like modulations of the bottomside F layer height marked by white arrows can be clearly seen between 22 and 24 UT.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Figure d shows the F layer true height as observed by the Digisonde at specific plasma frequencies (3.0–6.5 MHz) over Sao Luis, plotted from 18 to 24 UT. There was a clear downward phase propagation (marked with a dashed line), which identifies the possible presence of atmospheric gravity waves (AGWs) (Abdu et al, ; Mandal et al, ). Furthermore, Figure e shows a keogram plot of detrended TEC as a function of latitude and time at 48°W longitude that around the EPBs region.…”
Section: Discussionmentioning
confidence: 99%
“…From their study of the occurrence statistics, it was found that the percentage of days when waves in the spectral periods of gravity wave range occurred was greater for times of relatively higher solar activity duration (in 2013) compared to those of low solar activity (in 2011) (Laskar et al 2015). Furthermore, by using a new method to extract neutral gravity wave information from digisonde measurements (Mandal et al 2019), vertical wave propagation speeds and vertical scale sizes of waves were diagnosed. These revealed the presence of a systematic enhancement in these parameters with solar flux ).…”
Section: Observation Of Coupling Processesmentioning
confidence: 99%